Recent advances in alcohol-related liver disease (ALD): summary of a Gut round table meeting - Avila, Matias A; Dufour, Jean-François; Gerbes, Alexander L; Zoulim, Fabien; Bataller, Ramon; Burra, Patrizia; Cortez-Pinto, Helena; Gao, Bin; Gilmore, Ian; Mathurin, Philippe; Moreno, Christophe; Poznyak, Vladimir; et al. (Gut, 2020)
Alcohol-related liver disease (ALD), which includes a range of disorders of different severity and is one of the most prevalent types of liver disease worldwide, has recently regained increased attention. Among other reasons, the realisation that any alcohol intake, regardless of type of beverage represents a health risk, and the new therapeutic strategies tested in recently published or undergoing clinical trials spur scientific interest in this area.In April 2019, Gut convened a round table panel of experts during the European Association for the Study of the Liver International Liver Congress in Vienna to discuss critical and up-to-date issues and clinical trial data regarding ALD, its epidemiology, diagnosis, management, pathomechanisms, possible future treatments and prevention. This paper summarises the discussion and its conclusions.